KONSEP TEORI IMOGENE M. KING DAN MENGAPLIKASIKAN DALAM KASUS KEPERAWATAN - Abdilah Septiana Putri; Irna Nursanti (Nusantara Hasana Journal, 2024)
King uses a systems approach in developing conceptual systems and middle-range theory, namely the theory of goal achievement. King notes that “several scientists who have studied systems have noted that the only way to study humans interacting with the environment is to devise a conceptual framework of interdependent variables and interrelated concepts. King views humans as an open system that interacts with the environment, allowing objects, energy and information to freely influence it. In its conceptual framework, it includes three dynamic systems of interaction as individuals are called personal systems, when these individuals unite in groups it is called interpersonal systems. To deal with the problem of the patient's anxiety level, the nurse should explain the definition of the patient's illness, the risk factors that cause MCI in the patient, what examinations the patient should carry out, management and treatment for the patient. The nursing diagnosis of a knowledge deficit will decrease or decrease if the nurse has provided an explanation to the patient regarding the disease and how to treat it so that the patient no longer experiences a knowledge deficit. King's theory can describe a mutualistic relationship within a health team to achieve nursing care goals, where the individuals involved are also decision makers. It still covers a broad (general) scope, so its interpretation or application requires a clear understanding of the concept.